Vegetative propagation of Quercus suber L. by somatic embryogenesis. II. Plant regeneration from selected cork oak trees. (Plant cell reports, 2003)
The regeneration of somatic seedlings from selected 100-year-old cork oak trees is reported. The induction of somatic embryogenesis from leaves of epicormic shoots was significantly affected by genotype, harvesting time and their interaction. Leaves from all five selected trees produced somatic embryos when the segments of branches used as sources of epicormic shoots were collected in May. Genotype, but not the level of photosynthetically active radiation, affected the proliferation of the embryogenic lines and the number of detachable embryos that could be obtained from them. Genotype also affected several steps leading to conversion of somatic embryos, from germination to complete acclimatisation of somatic seedlings. Almost 40% of the somatic embryos from all lines germinated, showing coordinated root and shoot growth. Although the mean percentage of recovery for the whole process was low, plants could be regenerated from four of the five trees tested.